Textile sustainable development related to culture: a scientometric approach - Cui, Can; Nazlina, Shaari; Sazrinee, Zainal Abidin; Noor Azizi, Mohd Ali (idd3, 2024)
The sustainable development of textiles has been a notable concern for the textile industry and society in recent years. From green textiles and circular textiles to cultural textiles, academia has conducted many explorations. The problem of the connection between the cultural needs of increasingly educated consumers and the development of textiles has become increasingly prominent, which has also triggered many new social problems. This study aims to explore how culture promotes sustainability in textiles and can meet consumer demands. This study uses scientometric methods to conduct a thematic analysis of cultural factors in the development of textiles. From 2013 to 2023, the Web of Science and Scopus databases included a total of 306 articles related to the cultural factors in textiles. The results of this study are as follows: 40 main research keyword clusters appeared in the knowledge base, 6 research themes were identified, and a conceptual framework of culture in the development of textiles was constructed. At the same time, this study provides suggestions on how to better establish communication between textiles and culture. The results of this study will help textile practitioners better understand the current status, hot spots, and research trends of cultural sustainability in the textile industry while establishing closer connections with consumers. © 2024, idd3. All rights reserved.